Space truss is a three dimensional structure, which can draw forces work on its member either tension or compression without torsion. Space truss is favorable to build a large, light and stiff structure, which are made from relatively short bars. This research is a feasibility study of using bamboo as space truss members. This study focuses on designing bamboo connection, that strong enough for both tension and compression. According to the analysis done, bamboo culm with diameter 4 cm and 6 - Gina Gina Bachtiar; Surjono Surjokusumo; Naresworo Nugroho; Yusuf Sudo Hadi (Forum Pasca Sarjana, 2008)
Space truss is a three dimensional structure, which can draw forces work on its member either tension or compression without torsion. Space truss is favorable to build a large, light and stiff structure, which are made from relatively short bars. This research is a feasibility study of using bamboo as space truss members. This study focuses on designing bamboo connection, that strong enough for both tension and compression. According to the analysis done, bamboo culm with diameter 4 cm and 6 cm could be use to make space truss member for a simple 3m x 4 m canopy structure. The critical point of failure was on shear, because the shear strength of bamboo observed was only 3.9kg/cm2. Designing with uniform length members of one meter, it’s found that for bamboo of 4 cm and 6 cm in diameter, depth of shear area of 5 cm and 3 cm, respectively, are needed. Keywords: bamboo connection, space truss member, tension, compression